2001
DOI: 10.1016/s0370-2693(01)00460-9
|View full text |Cite
|
Sign up to set email alerts
|

On the relativistic origin of the kink effect in the chain of Pb isotopes

Abstract: We investigate the origin of the kink effect (KE) in the relativistic mean field theory by transforming the single-particle Dirac equation into a Schrödinger-like equation. It is found that relativistic self-consistent effects as well as contributions coming from the ρ meson determine the actual structure of the KE. However, the spin-orbit force generated by the ρ meson has no significant influence on the KE. On the other hand, in Refs. [3,4] the anomalous behavior of the charge radii of these isotopes has bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
3
1
1
Order By: Relevance
“…It is worth noting that a decrease of K by means of a mechanism different from the one we have found here, which is based on the m * σ dependence on the density, will not necessarily produce the same increase of the KE 6) . In particular, one can expect that the KE will depend also on the specific form of the E(ρ B )/A for ρ B < ρ 0 , since this region has a strong influence on the value of r c .…”
Section: The Compressibility Modulus Kcontrasting
confidence: 60%
See 2 more Smart Citations
“…It is worth noting that a decrease of K by means of a mechanism different from the one we have found here, which is based on the m * σ dependence on the density, will not necessarily produce the same increase of the KE 6) . In particular, one can expect that the KE will depend also on the specific form of the E(ρ B )/A for ρ B < ρ 0 , since this region has a strong influence on the value of r c .…”
Section: The Compressibility Modulus Kcontrasting
confidence: 60%
“…The RHA may provide a good description of the isotopic shift of the charge radii in the above-mentioned chain [5]. In a previous paper [6], we also addressed this question in the RHA. It was found that relativistic self-consistent effects as well as contributions coming from the ρ vector meson are important in determining the actual structure of the anomalous KE, both in linear and nonlinear models.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cette analyse confirme d'une part l'aptitude des modèles non relativistes à décrire des effets fins sur les rayons qui ne sont pas le seul fait des modèles relativistes [281] et d'autre part l'importance des corrélations tels que celles dues au mouvement du centre de masse qu'il faut désormais prendre en compte de manière systématique.…”
Section: Décalages Isotopiques Sur Les Rayons De Chargeunclassified
“…This is a consequence of the shell structure of nuclei. The fact that the density-dependent Hartree-Fock model with standard Skyrme functionals [1] or Gogny forces [2] were not able to reproduce this effect for the Pb isotopic chain, for example, whereas the relativistic models in the simple mean-field approach did reasonably well [3,4], has increased the interest in understanding the mechanism responsible for the KE [5][6][7][8]. However, it seems that the full theoretical understanding has not been reached yet.…”
Section: Introductionmentioning
confidence: 99%